New energy vehicle cable and preparation method thereof

By using twin-screw extruders to mix insulating materials and other additives in cables for new energy vehicles, a cladding inner layer is formed, and an intermediate grid layer and protective outer layer are built on it, the problems of cable heat dissipation, electromagnetic shielding and mechanical strength are solved, and more efficient heat dissipation and electromagnetic shielding are achieved, and the service life of the cable is extended.

CN119786166AActive Publication Date: 2025-04-08ANGREEN DONGGUAN NEW MATERIALS TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510128613.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-04-08
Estimated Expiration
2045-02-05

AI Technical Summary

Technical Problem

New energy vehicle cables lack heat dissipation capabilities during high power transmission or long-term working, limited electromagnetic shielding effect, poor mechanical strength, resulting in material aging and fire risk.

Method used

A method for preparing a new energy vehicle cable is adopted, including mixing insulating materials, flame retardants, toughening agents and antioxidants in a twin-screw extruder to form a coated inner layer; covering the mask plate and functional coating on the coated inner layer to form an intermediate grid layer; then wrapping the coated inner layer with the intermediate grid layer on the inner core, immersing it in the resin mixed solution to cure to form a protective outer layer.

Benefits of technology

It improves the thermal conductivity, electromagnetic shielding effect and mechanical strength of the cable, enhances the heat dissipation ability, reduces electromagnetic interference, and extends the service life of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786166A_ABST
    Figure CN119786166A_ABST
Patent Text Reader

Abstract

The invention provides a cable for a new energy vehicle and a preparation method thereof, and the preparation method comprises the following steps: placing an insulating material, a flame retardant, a flexibilizer and an antioxidant in a double-screw extruder, uniformly mixing and extruding, and cooling to form a coating inner layer; the wrapping inner layer is covered with a first-direction mask plate and coated with a first functional coating, after curing, the wrapping inner layer is covered with a second-direction mask plate and coated with a second functional coating, and a middle grid layer is formed on the wrapping inner layer; the wrapping inner layer with the middle grid layer is wound on an inner core of the cable for the new energy vehicle and then immersed in a resin mixed solution, the resin mixed solution enters the filling space and is cured to form a protective outer layer, and the cable for the new energy vehicle is obtained. Therefore, the heat dissipation capability, the electromagnetic shielding effect and the mechanical strength of the cable for the new energy vehicle are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of cable materials, and in particular relates to a cable for new energy vehicles and a preparation method thereof. Background Art

[0002] Cables for new energy vehicles are usually composed of an inner core, an insulation layer, a shielding layer, and an outer sheath layer. The operating voltage of new energy vehicle battery packs is usually as high as 400V~800V, and some high-performance models even exceed 1000V. The drive motor and fast charging system need to carry a large current, usually 200A~400A. Therefore, the conductor resistance of cables for new energy vehicles should comply with national or international standards, such as GB / T5013 or ISO6722.

[0003] First, the thermal conductivity in the existing technology mainly relies on metal conductors, but the interface thermal conductivity resistance between the inner core and the insulation layer is high, and the insulation layer and the outer sheath layer are usually made of polymer materials with low thermal conductivity, which hinders the heat from dissipating outward. When the cable is transmitting high power or working for a long time, heat accumulates inside, causing overheating, which may cause material aging or even fire. Secondly, a single shielding layer (such as metal foil) has limited suppression effect on wide-band electromagnetic interference, especially for high-frequency interference (GHz level). Finally, flexible polymers are often selected as materials for the insulation layer and the outer sheath, but these materials have limited wear resistance, impact resistance and vibration resistance, and poor mechanical properties. Cables are prone to aging, deformation, or even breakage under long-term vibration, high temperature or external force. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a new energy vehicle cable and a preparation method thereof, aiming to solve the problems of poor heat dissipation capacity, electromagnetic shielding effect and mechanical strength of the new energy vehicle cable.

[0005] In order to solve the above problems, the present invention proposes a method for preparing a cable for new energy vehicles, the steps comprising: S1, placing an insulating material, a flame retardant, a toughening agent and an antioxidant in a twin-screw extruder, mixing and evenly extruding, and cooling to form a coating inner layer, wherein the mixing temperature is 180-230° C., and the mixing time is 5-10 min; S2, first covering the inner layer of the coating with a mask plate in the first direction, coating the first functional coating, and then covering the mask plate in the second direction after curing, coating the second functional coating, and forming an intermediate grid layer on the inner layer of the coating, wherein the first functional coating and the second functional coating in the intermediate grid layer are cross-arranged and enclosed to form a filling space, and the first functional coating or the second functional coating includes at least one of a graphene dispersion, a carbon nanotube dispersion, a silver-plated copper powder coating, a boron nitride dispersion, a silicon carbide dispersion, a carbon fiber reinforced resin, and a nano zirconium oxide coating; S3. Wrap the coated inner layer with the intermediate grid layer around the inner core of the new energy vehicle cable, and then immerse it in a resin mixed solution. The resin mixed solution enters the filling space and solidifies to form a protective outer layer to obtain the new energy vehicle cable, wherein the resin mixed solution includes a thermoplastic resin matrix, an anti-UV additive and a wear-resistant enhancer, and the curing temperature of the resin mixed solution is 180~250℃.

[0006] In some embodiments of the present invention, in step S2, there is an acute angle A between the extension direction of the first functional coating and the extension direction of the second functional coating, the acute angle A is 30~90°, and the opening apertures of the first direction mask plate and the second direction mask plate are 1~3 mm.

[0007] In some embodiments of the present invention, step S2 includes: S2.1, preparing a first functional coating and performing ultrasonic dispersion, coating the inner layer after covering it with a first direction mask plate, and obtaining a first functional coating after curing; S2.2. Add magnetically responsive particles into the second functional coating and mix evenly, place the coating inner layer with the first functional coating in a directional magnetic field, cover the first functional coating with a second directional mask plate and then apply the second functional coating, and form an intermediate grid layer after curing to obtain the coating inner layer with the intermediate grid layer, wherein the internal particles of the second functional coating are arranged in a directionally arranged manner.

[0008] In some embodiments of the present invention, the curing temperature of the first functional coating and the second functional coating are both 150-180° C., and the thickness of the first functional coating and the second functional coating are both 0.05-0.1 mm; In step S2.1, the ultrasonic power of the ultrasonic dispersion is 200-400 W, and the ultrasonic time is 10-30 min; In step S2.2, the magnetic field direction of the oriented magnetic field remains parallel or perpendicular to the extension direction of the second functional coating, the magnetic responsive particles include at least one of ferroferric oxide particles, iron silicon aluminum particles, iron-based alloy particles, and cobalt ferrite particles, and the particle size of the magnetic responsive particles is 100~500nm.

[0009] In some embodiments of the present invention, calculated by weight percentage, in the step S1, the insulating material accounts for 50-70wt%, the flame retardant accounts for 10-20wt%, the toughening agent accounts for 3-9wt%, and the antioxidant accounts for 0.1-1wt%. The insulating material includes at least one of cross-linked polyethylene, polyimide, high-density polyethylene, and ethylene-vinyl acetate copolymer; the flame retardant includes at least one of aluminum hydroxide, magnesium hydroxide, flame-retardant silicone composite materials, red phosphorus, and phosphonates; the toughening agent includes at least one of ethylene-vinyl acetate copolymer, styrene-ethylene-butylene-benzene block copolymer, polyacrylate copolymer, and maleic anhydride grafted polyolefin; and the antioxidant includes at least one of butylated hydroxytoluene, dilauric acid dithiodipropyl ester, and triphenyl phosphate.

[0010] In some embodiments of the present invention, calculated by weight percentage, in the resin mixed solution of step S3, the thermoplastic resin matrix accounts for 70~90wt%, the anti-UV additive accounts for 3~5wt%, and the wear-resistant enhancer accounts for 3~7wt%. The thermoplastic resin matrix includes at least one of polyurethane, polyethylene, polypropylene, and polybutylene terephthalate, the anti-UV additive includes at least one of a hindered amine light stabilizer and a benzotriazole UV absorber, and the wear-resistant enhancer includes at least one of nano-alumina, nano-silicon dioxide, and polytetrafluoroethylene micropowder.

[0011] In some embodiments of the present invention, step S1 comprises: S1.1, Silane coupling agent is used to modify the surface of the flame retardant. The amount of silane coupling agent added is 1~3wt% of the weight of the flame retardant. S1.2. Place the insulating material in a vacuum dryer and dry it at 60-80°C for 4-6 hours to reduce the moisture content of the insulating material to ≤0.1wt%; S1.3, use a high-speed stirrer to evenly stir the toughening agent and antioxidant at a speed of 1000-1500 rpm for 30-60 min; S1.4. First, add the insulating material into the main hopper of the twin-screw extruder, add the flame retardant in batches through the side hopper, and add the mixture of toughening agent and antioxidant through the special additive injection port after the insulating material is stably melted, mix and cool to obtain the coating inner layer.

[0012] In some embodiments of the present invention, step S3 includes: S3.1, drying the thermoplastic resin matrix at a temperature of 80-100°C for 4-6 hours to reduce the moisture content to ≤0.05wt%; S3.2, adding the anti-UV additive, the wear-resistant enhancer and the diluent to the thermoplastic resin matrix in sequence, premixing for 20 to 30 minutes at a speed of 1000 to 1500 rpm using a high-speed stirrer to obtain a resin mixed solution with a viscosity of 500 to 1500 mPa·s; S3.3, heating the resin mixed solution at a constant temperature, equipping with a rotating fixture, fixing the inner core wrapped with the coated inner layer with the intermediate grid layer on the fixture and slowly immersing it in the resin mixed solution, wherein the constant temperature of the resin mixed solution is 60-80°C, the rotation angle of the rotating fixture is 45-90°, the immersion speed is 1-3 mm / s, and the immersion time is 5-10 min; S3.4, after the immersion is completed, the inner layer of the coating is slowly removed, and a low-speed rotating device is used to perform a solution shedding operation, so that the thickness of the resin solution on the surface of the inner layer of the coating is 0.2-2 mm, wherein the rotation speed of the low-speed rotating device is 30-50 rpm; S3.5. Place the inner layer of the coating after peeling off in a vacuum chamber for degassing. After degassing, place it in a hot air circulation curing furnace for low-temperature circulation pre-curing. After cooling, obtain a cable for new energy vehicles, wherein the degassing air pressure is -0.08~-0.1MPa, the degassing time is 3~5min, the curing temperature includes a first stage of 180~200℃, a second stage of 200~220℃ and a third stage of 220~250℃, the curing time of the first stage is 20~25min, and the curing time of the second stage and the third stage is 10~20min.

[0013] The present invention proposes a cable for new energy vehicles, which is prepared by the preparation method of the cable for new energy vehicles as described above, and the cable for new energy vehicles includes an internal conductor, a coating inner layer, an intermediate mesh layer and a protective outer layer which are stacked in sequence, wherein the internal conductor is used to realize signal or energy transmission, the coating inner layer is used to protect the internal conductor of the cable for new energy vehicles, the intermediate mesh layer is used to improve the thermal conductivity, electrical conductivity and structural strengthening capabilities of the cable for new energy vehicles, and the protective outer layer is used to improve the durability of the cable for new energy vehicles and ensure the long-term use performance of the cable in complex environments.

[0014] Compared with the prior art, the cable for new energy vehicles and the preparation method thereof in the present invention have the following beneficial effects: The first functional coating and the second functional coating may contain thermal conductive materials, which are cross-arranged to form a thermal conductive path, improve the thermal conductivity of the material, and facilitate heat dissipation of new energy vehicle cables under high current load. The cross-grid design of the thermal conductive path effectively reduces the interfacial thermal resistance and ensures uniform diffusion of heat flow. If the coating contains graphene dispersion, carbon nanotube dispersion or silver-plated copper powder coating, the cross structure forms an efficient conductive network, enhances the electromagnetic shielding effect of the material, and reduces electromagnetic interference. The cross-setting of the middle grid layer provides additional mechanical support, disperses external forces, and improves the compression and bending resistance of the cable. Carbon fiber reinforced resin or nano zirconium oxide coating in the coating further improves impact resistance and wear resistance. The multi-layer structure formed after the cavity is filled effectively alleviates the difference in thermal expansion coefficients, reduces the problem of interface stress concentration, and extends the service life of the cable. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a schematic flow chart of a method for preparing a cable for a new energy vehicle in one embodiment of the present invention; Figure 2 It is a schematic structural diagram of the middle mesh layer in the cable for new energy vehicles in one embodiment of the present invention; Figure 3 is a schematic structural diagram of an intermediate mesh layer in a cable for new energy vehicles in another embodiment of the present invention; Figure 4 is a schematic structural diagram of an intermediate mesh layer in a cable for new energy vehicles in another embodiment of the present invention; Figure 5 is a schematic structural diagram of an intermediate mesh layer in a cable for new energy vehicles in another embodiment of the present invention; Figure 6 It is a structural schematic diagram of a first direction mask plate and a second direction mask plate in a method for preparing a cable for a new energy vehicle in one embodiment of the present invention; Figure 7 It is a structural schematic diagram of a first direction mask plate and a second direction mask plate in a method for preparing a cable for new energy vehicles in another embodiment of the present invention.

[0016] In the accompanying drawings, each reference numeral represents: 100. Cables for new energy vehicles; 10. Inner core; 20. Inner coating layer; 30. Intermediate mesh layer; 31. First functional coating; 32. Second functional coating; 33. Filling space; 40. Protective outer layer; 201. First direction mask plate; 202. Second direction mask plate. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0018] Please refer to Figure 1 The present invention proposes a method for preparing a cable 100 for a new energy vehicle, the steps comprising: S1, placing the insulating material, flame retardant, toughening agent and antioxidant in a twin-screw extruder, extruding them uniformly after mixing, and forming the coating inner layer 20 after cooling, wherein the mixing temperature is 180-230°C, for example, 180°C, 200°C, 230°C, and the mixing time is 5-10min, for example, 5min, 8min, 10min. In this embodiment, the specific structure of the twin-screw extruder used is known to those skilled in the art and will not be repeated here.

[0019] By providing the appropriate temperature, the insulating material is ensured to be completely melted, providing a good matrix environment for the uniform dispersion of flame retardants, toughening agents and antioxidants. Ensure that the mixing time is long enough to evenly distribute the components and avoid material stratification or local agglomeration. Appropriate temperature and time can ensure a good combination of flame retardants and insulating materials. Through appropriate mixing temperature and time, the toughening agent is evenly dispersed in the matrix of the insulating material, thereby improving the impact resistance of the composite material and enhancing the tensile strength and ductility of the material. The antioxidant is evenly dispersed during the mixing process, which can improve the antioxidant performance of the composite material, thereby delaying the aging of the material under high temperature or light environment.

[0020] Calculated by weight percentage, in step S1, the insulating material accounts for 50-70wt%, such as 50wt%, 60wt%, and 70wt%, the flame retardant accounts for 10-20wt%, such as 10wt%, 15wt%, and 20wt%, the toughening agent accounts for 3-9wt%, such as 3wt%, 6wt%, and 9wt%, and the antioxidant accounts for 0.1-1wt%, such as 0.1wt%, 0.5wt%, and 1wt%. The insulating material includes at least one of cross-linked polyethylene, polyimide, high-density polyethylene, and ethylene-vinyl acetate copolymer, the flame retardant includes at least one of aluminum hydroxide, magnesium hydroxide, flame-retardant siloxane composite material, red phosphorus, and phosphonate, the toughening agent includes at least one of ethylene-vinyl acetate copolymer, styrene-ethylene-butylene-benzene block copolymer, polyacrylate copolymer, and maleic anhydride grafted polyolefin, and the antioxidant includes at least one of butylated hydroxytoluene, dilauric acid disulfide dipropyl ester, and triphenyl phosphate.

[0021] In one embodiment of the present invention, step S1 includes: S1.1. Surface modification of the flame retardant with a silane coupling agent, wherein the amount of the silane coupling agent added is 1-3 wt % of the weight of the flame retardant, for example, 1 wt %, 2 wt %, or 3 wt %. The silane coupling agent may be at least one of aminosilane, hydroxysilane, mercaptan silane, epoxy silane, and alkoxy silane.

[0022] Silane coupling agents significantly improve the dispersion of flame retardants in insulating material matrix and avoid particle agglomeration by forming an active coating on the surface of flame retardants. The organic groups of silane coupling agents are highly compatible with insulating materials, and the inorganic groups are chemically bonded to the surface of flame retardants, thereby improving the interfacial bonding between the flame retardant and the matrix. Surface modification can reduce the moisture release of flame retardants during processing, reduce thermal degradation or bubble generation, and ensure the flame retardant properties of the final product. The modified flame retardant is more evenly distributed, reducing stress concentration in the matrix material and improving the overall strength and toughness of the material.

[0023] S1.2, placing the insulating material in a vacuum dryer, drying at a temperature of 60-80°C for 4-6 hours to reduce the moisture content of the insulating material to ≤0.1wt%, the drying temperature can be 60°C, 70°C, 80°C, and the drying time can be 4h, 5h, 6h. In this embodiment, the specific structure of the vacuum desiccant used is known to those skilled in the art and will not be repeated here.

[0024] Vacuum drying effectively removes residual moisture from the insulating material, reducing the moisture content to ≤0.1wt%, avoiding bubbles or micropores in the subsequent processing. The reduction in water content reduces the dielectric loss and conductivity risk of the material, ensuring that the cable material has stable insulation performance. The insulating material after drying has better fluidity and can be fully mixed with flame retardants and toughening agents during mixing, improving processing efficiency and product quality. Low moisture content reduces the risk of hydrolysis of the material during use and extends the service life of the product in humid or high temperature environments.

[0025] S1.3, using a high-speed stirrer to uniformly stir the toughening agent and antioxidant at a speed of 1000-1500 rpm for 30-60 min, the speed can be 1000 rpm, 1200 rpm, 1500 rpm, and the stirring time can be 30 min, 40 min, 60 min. In this embodiment, the specific structure of the high-speed stirrer used is known to those skilled in the art and will not be repeated here.

[0026] High-speed stirring at a speed of 1000~1500rpm can fully disperse the toughening agent and antioxidant to form a uniformly mixed masterbatch to ensure the subsequent mixing effect. The uniformly distributed toughening agent can effectively reduce the brittleness of the material and improve the impact resistance and ductility of the cable. Uniform stirring prevents the agglomeration of the antioxidant and ensures that the antioxidant components are evenly distributed in the material, thereby improving the anti-aging performance of the material. The synergistic effect of the components is optimized during the stirring process, laying the foundation for subsequent mixing and molding, and ensuring the mechanical properties and chemical stability of the material.

[0027] S1.4. The insulating material is first added to the main hopper of the twin-screw extruder, and the flame retardant is added in batches through the side hopper. After the insulating material is stably melted, the mixture of the toughening agent and the antioxidant is added through the special additive injection port, mixed, and cooled to obtain the coating inner layer 20.

[0028] The twin-screw extruder ensures that the insulating material, flame retardant, toughening agent and antioxidant are evenly mixed through strong shearing and high-temperature melting to form a composite material with stable performance. Through high-temperature mixing, the flame retardant is fully contacted with the base material to form a uniformly distributed flame retardant barrier layer, which effectively improves the flame retardant properties of the material. The toughening agent melts and disperses under high temperature conditions, forming a close bond with the base material, significantly improving the tensile strength and toughness of the coated inner layer 20. The design of adding flame retardants in batches ensures mixing efficiency and avoids blockage or uneven mixing caused by excessive instantaneous addition. The evenly distributed antioxidant can protect the stability of the material during high-temperature processing and subsequent use, delay material aging, and maintain long-term excellent insulation performance. The coated inner layer 20 obtained after extrusion cooling serves as the basic protective layer of the cable, which can resist mechanical shock and environmental factors and provide a stable base for the intermediate mesh layer 30.

[0029] S2. First, cover the inner layer 20 with a first direction mask plate 201, apply the first functional coating 31, and then cover the inner layer 20 with a second direction mask plate 202 after curing, and apply the second functional coating 32 to form an intermediate grid layer 30 on the inner layer 20, wherein the first functional coating 31 and the second functional coating 32 in the intermediate grid layer 30 are cross-arranged and enclosed to form a filling space 33, and the first functional coating 31 or the second functional coating 32 includes at least one of a graphene dispersion, a carbon nanotube dispersion, a silver-plated copper powder coating, a boron nitride dispersion, a silicon carbide dispersion, a carbon fiber reinforced resin, and a nano zirconium oxide coating.

[0030] The first functional coating 31 and the second functional coating 32 may contain heat-conducting materials, which are cross-arranged to form a heat-conducting path, improve the thermal conductivity of the material, and facilitate the heat dissipation of the cables of new energy vehicles under high current loads. The cross-grid design of the heat-conducting path effectively reduces the interfacial thermal resistance and ensures uniform diffusion of heat flow. If the coating contains graphene dispersion, carbon nanotube dispersion or silver-plated copper powder coating, the cross structure forms an efficient conductive network, enhances the electromagnetic shielding effect of the material, reduces electromagnetic interference, improves the antistatic performance of the material, and avoids the influence of static electricity accumulation on cable operation.

[0031] The cross arrangement of the middle grid layer 30 provides additional mechanical support, disperses external forces, and improves the compression and bending resistance of the cable. The carbon fiber reinforced resin or nano zirconium oxide coating in the coating further improves the impact resistance and wear resistance. The multi-layer structure formed after the cavity is filled effectively alleviates the difference in thermal expansion coefficient, reduces the problem of interface stress concentration, and prolongs the service life of the cable.

[0032] The filling space 33 formed by the first functional coating 31 and the second functional coating 32 provides a fixed space for filling the resin mixed solution to ensure uniform filling. The regular shape of the cavity and the cross-network design help control the flow of resin in the subsequent filling process, prevent bubbles from remaining, and improve product quality.

[0033] Boron nitride and silicon carbide have excellent high temperature resistance, and the intermediate mesh layer 30 formed after coating can provide thermal stability in high temperature environments. The nano zirconium oxide coating improves the corrosion resistance of the intermediate layer, making the cable material suitable for more severe chemical or humid environments.

[0034] The materials of the first direction mask plate 201 and the second direction mask plate 202 can be polymer materials such as polyimide film and polytetrafluoroethylene film, which are reusable and suitable for multiple coating processes after anti-sticking treatment on the surface, and are suitable for scenes requiring high temperature and high mechanical strength.

[0035] In other embodiments, please refer to Figures 2 to 7 The first functional coating 31 can be arranged continuously or at intervals, and the openings of the first direction mask plate 201 and the second direction mask plate 202 can also be arranged in an intermittent arrangement or in a continuous form, so as to be suitable for different actual usage situations. The shapes shown in the above figures are only partial examples. In the present invention, the specific opening shapes of the first direction mask plate 201 and the second direction mask plate 202 are not limited, nor are the specific shapes of the first functional coating 31 and the second functional coating 32.

[0036] In one embodiment, step S2 includes: S2.1. Modulate the first functional coating 31 and perform ultrasonic dispersion, cover the first direction mask plate 201 on the inner layer 20 and then apply it, and obtain the first functional coating after curing. The ultrasonic power of ultrasonic dispersion is 200~400W, for example, it can be 200W, 300W, 400W, and the ultrasonic time is 10~30min, for example, it can be 10min, 20min, 30min.

[0037] Ultrasonic waves break the agglomeration of particles in the coating through the cavitation effect, so that graphene dispersion, carbon nanotube dispersion, silver-plated copper powder coating, etc. are evenly distributed in the coating matrix, improving the uniformity of the coating and avoiding local excessive concentration or functional loss. The strong shear force of ultrasound breaks down large-sized particles into nano-sized particles (for example, reducing the particle diameter to a range of 10-50nm), enhancing the surface activity of the coating. Improve the functional properties of the coating, such as thermal conductivity (by reducing the interfacial thermal resistance) or electrical conductivity (by forming a continuous conductivity path).

[0038] Ultrasonic treatment can promote the interaction between functional particles and dispersants, form a stable dispersion system, avoid particle sedimentation or aggregation, improve the construction performance of the coating in the subsequent coating process, and ensure uniform coating thickness.

[0039] The first direction mask plate 201 is used to ensure the regular shape and distribution of the coating to avoid disordered or redundant coating. It provides a clear functional area and lays the foundation for the subsequent cross-coating of the second functional coating 32. The curing process after coating forms a strong interface bond between the coating matrix and the coated inner layer 20 through high temperature treatment (usually 150~200℃), enhances the mechanical stability and durability of the coating, and prevents it from falling off or warping. The regular coating of the first functional coating provides precise positioning for the cross-grid design of the second direction functional coating, so that the intermediate grid layer 30 has higher structural and functional integrity.

[0040] Effect of ultrasonic power (200~400W): Low power (200W): Suitable for dispersing lightweight materials (such as graphene or carbon nanotubes), avoiding damage to the nanosheet structure caused by excessive ultrasonic power. High power (400W): Suitable for dispersing larger or denser particles (such as silver-coated copper powder, nano zirconium oxide), ensuring their full dispersion.

[0041] Effect of ultrasonic time (10~30min): Short time (10min): Keep the particle structure intact, suitable for functional coatings that are sensitive to particles (such as carbon nanotube dispersions). Long time (30min): Completely disperse high-viscosity coatings or large particles to avoid particle agglomeration.

[0042] S2.2, add magnetic response particles to the second functional coating 32 and mix them evenly, place the coated inner layer 20 with the first functional coating in an oriented magnetic field, cover the first functional coating with a second directional mask plate 202 and then apply the second functional coating 32, and after curing, form an intermediate grid layer 30, and obtain the coated inner layer 20 with the intermediate grid layer 30, wherein the internal particles of the second functional coating are arranged in a directional manner. The magnetic field direction of the oriented magnetic field is parallel or perpendicular to the extension direction of the second functional coating 32, and the magnetic response particles include at least one of ferroferric oxide particles, iron silicon aluminum particles, iron-based alloy particles, and cobalt ferrite particles, and the particle size of the magnetic response particles is 100~500nm, for example, it can be 100nm, 300nm, 500nm.

[0043] The magnetically responsive particles are arranged in a specific direction under the action of a directional magnetic field to form a continuous heat conduction path. Parallel magnetic field: The heat conduction path is arranged along the extension direction, which is suitable for improving the longitudinal thermal conductivity of the coating and optimizing the efficiency of heat transfer from the inside of the cable to the outside. Perpendicular magnetic field: The heat conduction path is arranged perpendicular to the extension direction, which helps to improve the heat diffusion capacity on the cross section. The magnetically responsive particles are arranged in a directional manner to reduce the interfacial thermal resistance caused by the disordered arrangement of particles during heat transfer. The thermal conductivity of the overall coating is improved, and the heat dissipation capacity of the cable under high current load conditions is enhanced.

[0044] The magnetically responsive particles have good electrical conductivity, and the directional magnetic field enables them to form a continuous conductive network. Parallel magnetic field: forms a low-impedance longitudinal conductive path to improve the conductivity of the coating. Perpendicular magnetic field: optimizes the lateral conductivity of the coating and can be used to enhance the electromagnetic shielding effect. The magnetically responsive particles are arranged to form a multi-level conductive shielding network that effectively reflects and absorbs external electromagnetic waves. Improve the coating's ability to resist electromagnetic interference and reduce the impact of the external environment on cable transmission signals.

[0045] The magnetic responsive particles are arranged in an orderly manner along the direction of the magnetic field, which improves the uniformity of the internal structure of the coating. It enhances the tensile, compression and bending resistance of the coating and avoids coating damage caused by stress concentration. The magnetic responsive particles with a particle size of 100~500nm are filled in the coating, which can significantly enhance the hardness and toughness of the coating. It prolongs the service life of the cable material, which is especially suitable for mechanical protection needs in complex working conditions.

[0046] In step S2, there is an acute angle A between the extension direction of the first functional coating 31 and the extension direction of the second functional coating 32, and the acute angle A is 30~90°, for example, 60°, 80°, 120°, and the aperture of the opening of the first direction mask plate 201 and the second direction mask plate 202 is 1~3mm, for example, 1mm, 2mm, 3mm.

[0047] Smaller acute angles A provide a higher density grid cross structure, which is suitable for application scenarios that require high thermal conductivity, ensuring that heat can be evenly transferred in multiple directions. The 90° acute angle A forms the most classic grid layout, providing balanced thermal conductivity and mechanical support capabilities. Larger acute angles A form relatively sparse cross grids, which are suitable for scenarios that require both thermal conductivity and lightweight. The thermal conductive coating forms a multi-directional heat conduction path in the cross grid, significantly improving the overall thermal diffusion capacity of the middle grid layer 30. The conductive coating forms a three-dimensional conductive channel in the grid intersection area, enhancing the electrical conductivity of the coating.

[0048] S3. Wrap the inner layer 20 with the middle mesh layer 30 on the inner core 10 of the new energy vehicle cable 100, and then immerse it in a resin mixed solution. The resin mixed solution enters the filling space 33 and forms a protective outer layer 40 after curing to obtain the new energy vehicle cable 100, wherein the resin mixed solution includes a thermoplastic resin matrix, an anti-UV additive and a wear-resistant enhancer, and the curing temperature of the resin mixed solution is 180~250℃.

[0049] The protective outer layer 40 forms a uniform protective layer through the solidification of the resin matrix, which significantly enhances the impact resistance and wear resistance of the cable. The wear-resistant enhancer is evenly distributed in the resin, improves the surface hardness, and prolongs the service life of the cable in complex environments.

[0050] The protective outer layer 40 can effectively isolate the inner layer of the cable from damage by moisture, dust and chemical corrosive substances. The dense structure formed by the thermoplastic resin matrix improves the waterproof and chemical corrosion resistance, and is particularly suitable for humid or high salt fog environments.

[0051] The anti-UV additive slows down the photodegradation process of the resin matrix by absorbing or reflecting ultraviolet rays. The protective outer layer 40 can maintain long-term flexibility and mechanical properties, extending the service life of the cable in outdoor environments. In the case of long-term exposure to sunlight, the outer layer is prevented from aging, cracking or becoming brittle.

[0052] The resin matrix forms a cross-linked or crystalline structure during the curing process at 180-250°C, which significantly improves thermal stability and prevents softening or deformation in high temperature environments. The protective outer layer 40 can withstand the heat generated internally when high-power current passes through. The anti-UV additives and wear-resistant enhancers evenly distributed in the resin mixed solution work synergistically to enhance the anti-aging performance of the protective outer layer 40. It resists the long-term effects of ultraviolet rays, oxidation and mechanical wear and delays the aging process.

[0053] The resin mixed solution enters the filling space 33 of the middle mesh layer 30 through an immersion process, forming a uniform filling without bubbles or gaps. The coating thickness and cavity filling amount are controlled to ensure the mechanical properties and stability of the overall structure. The resin matrix forms a strong interface bond with the middle mesh layer 30 during the curing process to avoid delamination. The bonding force between the coating and the middle mesh layer 30 is enhanced, providing higher anti-peeling performance.

[0054] The immersion process is simple and efficient, suitable for mass production and reduces production costs. The curing process can be completed quickly through a hot air circulation furnace or radiation heating, improving production efficiency.

[0055] Calculated by weight percentage, in the resin mixed solution of step S3, the thermoplastic resin matrix accounts for 70-90wt%, for example, 70wt%, 80wt%, 90wt%, the anti-UV additive accounts for 3-5wt%, for example, 3wt%, 4wt%, 5wt%, and the wear-resistant enhancer accounts for 3-7wt%, for example, 3wt%, 5wt%, 7wt%. The thermoplastic resin matrix includes at least one of polyurethane, polyethylene, polypropylene, and polybutylene terephthalate, the anti-UV additive includes at least one of hindered amine light stabilizer and benzotriazole UV absorber, and the wear-resistant enhancer includes at least one of nano-alumina, nano-silicon dioxide, and polytetrafluoroethylene micropowder.

[0056] In one embodiment of the present invention, in order to realize winding the coating inner layer 20 with the middle mesh layer 30 on the inner core 10 of the new energy vehicle cable 100, it can be realized in the following manner.

[0057] 1. A winding device using a tension control system, which may include a servo motor, a rotating shaft, etc., automatically adjusts the tension and winding speed of the inner layer 20 to evenly wind the inner layer 20 onto the surface of the inner core 10. The tension range can be adjusted according to the material properties, and the material is prevented from being loosened or stretched excessively during the winding process, so that high-precision control of the head-to-tail joint can be achieved.

[0058] 2. Adhesive auxiliary technology, such as hot melt adhesive bonding, pre-coating hot melt adhesive (such as modified polyester or polyurethane hot melt adhesive) on the inner surface of the coating inner layer 20, and melting the adhesive layer by local heating during the winding process to bond with the surface of the inner core 10. Or during the winding process, the coating inner layer 20 is bonded to the surface of the inner core 10 by spraying or coating a liquid adhesive (such as epoxy resin or silicone adhesive). The head and tail of the coating inner layer 20 can also be cut into an inclined surface (such as 30°~45°), and the head and tail are tightly spliced ​​by precise alignment and light pressure during the winding process, providing a larger contact area and high bonding strength. Then, a hot pressing device is used to apply hot pressing at the head and tail splicing of the coating inner layer 20, so that the material is locally melted and seamlessly bonded, and the joint is smooth without thickness protrusions.

[0059] The specific structures of all the mechanical devices used above are known to those skilled in the art and will not be described in detail here.

[0060] In one embodiment of the present invention, step S3 includes: S3.1. Dry the thermoplastic resin matrix at a temperature of 80-100°C, such as 80°C, 90°C, or 100°C, for a period of 4-6 hours, such as 4 hours, 5 hours, or 6 hours, to reduce the moisture content to ≤0.05wt%.

[0061] The moisture content of the thermoplastic resin matrix is ​​reduced to ≤0.05wt%, effectively avoiding bubbles due to water evaporation during subsequent heating or curing, ensuring the density of the material. After the moisture content is reduced, the bond between the resin and the middle grid layer 30 is more firm, improving the adhesion performance of the coating. Removing moisture can reduce hydrolysis reactions or material degradation, ensuring the long-term stability of the cable in a high temperature environment.

[0062] S3.2, add the anti-UV additive, wear-resistant reinforcing agent and diluent to the thermoplastic resin matrix in sequence, use a high-speed stirrer to premix for 20 to 30 minutes at a speed of 1000 to 1500 rpm, and obtain a resin mixed solution with a viscosity of 500 to 1500 mPa·s. The specific structure of the high-speed stirrer is known to those skilled in the art and will not be described here. The speed can be 1000 rpm, 1200 rpm, 1500 rpm, etc., the stirring time can be 20 min, 25 min, 30 min, and the viscosity of the resin mixed solution can be 500 mPa·s, 1000 mPa·s, 1500 mPa·s.

[0063] The anti-UV additive and the wear-resistant enhancer are fully dispersed during high-speed stirring to form a stable resin mixed solution, which avoids component separation or particle aggregation during subsequent use. The viscosity is controlled between 500 and 1500 mPa·s to ensure that the resin mixed solution can evenly penetrate into the filling space 33 of the middle mesh layer 30 during coating, while avoiding sagging. The uniform distribution of the anti-UV additive ensures the anti-ultraviolet performance of the protective outer layer 40, and the uniform distribution of the wear-resistant enhancer improves the surface hardness and scratch resistance, thereby extending the service life of the cable.

[0064] S3.3. Heat the resin mixed solution at a constant temperature, equip with a rotating clamp, fix the inner core 10 wrapped with the coating inner layer 20 with the intermediate mesh layer 30 on the clamp and slowly immerse it in the resin mixed solution, wherein the constant temperature of the resin mixed solution is 60~80℃, for example, it can be 60℃, 70℃, 80℃, the rotation angle of the rotating clamp is 45~90°, for example, it can be 45°, 50°, 90°, the immersion speed is 1~3mm / s, for example, it can be 1mm / s, 2mm / s, 3mm / s, and the immersion time is 5~10min, for example, it can be 5min, 8min, 10min.

[0065] Constant temperature heating maintains the fluidity of the resin mixed solution, and the slow immersion of the rotating fixture ensures that the solution evenly penetrates into the filling space 33 of the middle grid layer 30. Accurate control of the immersion speed and time avoids incomplete filling of the cavity due to too fast immersion, or excessive coating due to too slow immersion. The coordination of temperature and angle during immersion reduces air entrapment and ensures that the coating is free of bubbles or defects. Control the rotation and immersion depth of the fixture so that the resin mixed solution evenly covers the entire surface of the inner coating layer 20.

[0066] S3.4. After the immersion is completed, slowly take out the coating inner layer 20, and use a low-speed rotating device to perform a solution removal operation so that the thickness of the resin solution on the surface of the coating inner layer 20 is 0.2~2mm, for example, it can be 0.2mm, 1mm, 2mm, wherein the rotation speed of the low-speed rotating device is 30~50rpm, for example, it can be 30rpm, 40rpm, 50rpm.

[0067] The excess resin solution is removed by a low-speed rotating device to ensure that the thickness of the protective outer layer 40 is within the range of 0.22mm, which not only meets the mechanical protection requirements but also avoids material waste. The low-speed rotation allows the residual resin on the surface to flow evenly, avoiding uneven thickness or defects caused by local accumulation. The shedding process simplifies the manual adjustment process and is suitable for mass automatic production.

[0068] S3.5. Place the coated inner layer 20 after peeling off in a vacuum chamber for degassing. After degassing, place it in a hot air circulation curing furnace for low-temperature circulation pre-curing. After cooling, obtain the new energy vehicle cable 100, wherein the degassing time is 3~5min, 3min, 4min, 5min, and the curing temperature includes a first stage of 180~200℃, a second stage of 200~220℃, and a third stage of 220~250℃. The curing time of the first stage is 20~25min, and the curing time of the second and third stages is 10~20min.

[0069] The specific mechanical structures of all the devices used in step S3 are known to those skilled in the art and will not be described in detail here.

[0070] The present invention also proposes a cable 100 for new energy vehicles, comprising an inner coating layer 20, an intermediate mesh layer 30 and a protective outer layer 40, wherein the inner coating layer 20 is used to protect the internal conductor of the new energy vehicle cable 100 to prevent current leakage, the intermediate mesh layer 30 is used to improve the thermal conductivity, electrical conductivity and structural strengthening capabilities of the new energy vehicle cable 100, and the protective outer layer 40 is used to improve the durability of the new energy vehicle cable 100 to ensure the long-term use performance of the cable in complex environments.

[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a cable for a new energy vehicle, characterized in that the steps include: S1, placing an insulating material, a flame retardant, a toughening agent and an antioxidant in a twin-screw extruder, mixing and evenly extruding, and cooling to form a coating inner layer, wherein the mixing temperature is 180-230° C., and the mixing time is 5-10 min; S2, first covering the inner layer of the coating with a mask plate in the first direction, coating the first functional coating, and then covering the mask plate in the second direction after curing, coating the second functional coating, and forming an intermediate grid layer on the inner layer of the coating, wherein the first functional coating and the second functional coating in the intermediate grid layer are cross-arranged and enclosed to form a filling space, and the first functional coating or the second functional coating includes at least one of a graphene dispersion, a carbon nanotube dispersion, a silver-plated copper powder coating, a boron nitride dispersion, a silicon carbide dispersion, a carbon fiber reinforced resin, and a nano zirconium oxide coating; S3. Wrap the coated inner layer with the intermediate grid layer around the inner core of the new energy vehicle cable, and then immerse it in a resin mixed solution. The resin mixed solution enters the filling space and solidifies to form a protective outer layer to obtain the new energy vehicle cable, wherein the resin mixed solution includes a thermoplastic resin matrix, an anti-UV additive and a wear-resistant enhancer, and the curing temperature of the resin mixed solution is 180~250℃.

2. The method for preparing the cable for new energy vehicles according to claim 1, characterized in that: In the step S2, there is an acute angle A between the extension direction of the first functional coating and the extension direction of the second functional coating, the acute angle A is 30-90°, and the opening apertures of the first direction mask plate and the second direction mask plate are 1-3 mm.

3. The method for preparing a cable material for an energy vehicle according to claim 1 or 2, characterized in that: The step S2 comprises: S2.1, preparing a first functional coating and performing ultrasonic dispersion, coating the inner layer after covering it with a first direction mask plate, and obtaining a first functional coating after curing; S2.

2. Add magnetically responsive particles into the second functional coating and mix evenly, place the coating inner layer with the first functional coating in a directional magnetic field, cover the first functional coating with a second directional mask plate and then apply the second functional coating, and form an intermediate grid layer after curing to obtain the coating inner layer with the intermediate grid layer, wherein the internal particles of the second functional coating are arranged in a directionally arranged manner.

4. The method for preparing a cable material for an energy vehicle according to claim 3, characterized in that: The curing temperatures of the first functional coating and the second functional coating are both 150-180° C., and the thicknesses of the first functional coating and the second functional coating are both 0.05-0.1 mm; In step S2.1, the ultrasonic power of the ultrasonic dispersion is 200-400 W, and the ultrasonic time is 10-30 min; In step S2.2, the magnetic field direction of the oriented magnetic field remains parallel or perpendicular to the extension direction of the second functional coating, the magnetic responsive particles include at least one of ferroferric oxide particles, iron silicon aluminum particles, iron-based alloy particles, and cobalt ferrite particles, and the particle size of the magnetic responsive particles is 100~500nm.

5. The method for preparing the cable for new energy vehicles according to claim 1, characterized in that: Calculated by weight percentage, in the step S1, the insulating material accounts for 50-70wt%, the flame retardant accounts for 10-20wt%, the toughening agent accounts for 3-9wt%, and the antioxidant accounts for 0.1-1wt%. The insulating material includes at least one of cross-linked polyethylene, polyimide, high-density polyethylene, and ethylene-vinyl acetate copolymer; the flame retardant includes at least one of aluminum hydroxide, magnesium hydroxide, flame-retardant siloxane composite materials, red phosphorus, and phosphonates; the toughening agent includes at least one of ethylene-vinyl acetate copolymer, styrene-ethylene-butylene-benzene block copolymer, polyacrylate copolymer, and maleic anhydride grafted polyolefin; and the antioxidant includes at least one of butylated hydroxytoluene, dilauric acid dithiodipropyl ester, and triphenyl phosphate.

6. The method for preparing the cable for new energy vehicles according to claim 1, characterized in that: Calculated by weight percentage, in the resin mixed solution of step S3, the thermoplastic resin matrix accounts for 70-90wt%, the anti-UV additive accounts for 3-5wt%, and the wear-resistant enhancer accounts for 3-7wt%. The thermoplastic resin matrix includes at least one of polyurethane, polyethylene, polypropylene, and polybutylene terephthalate, the anti-UV additive includes at least one of a hindered amine light stabilizer and a benzotriazole UV absorber, and the wear-resistant enhancer includes at least one of nano-alumina, nano-silicon dioxide, and polytetrafluoroethylene micropowder.

7. The method for preparing a cable for new energy vehicles according to claim 1, characterized in that: The step S1 comprises: S1.1, Silane coupling agent is used to modify the surface of the flame retardant. The amount of silane coupling agent added is 1~3wt% of the weight of the flame retardant. S1.

2. Place the insulating material in a vacuum dryer and dry it at 60-80°C for 4-6 hours to reduce the moisture content of the insulating material to ≤0.1wt%; S1.3, use a high-speed stirrer to evenly stir the toughening agent and antioxidant at a speed of 1000-1500 rpm for 30-60 min; S1.

4. First, add the insulating material into the main hopper of the twin-screw extruder, add the flame retardant in batches through the side hopper, and add the mixture of toughening agent and antioxidant through the special additive injection port after the insulating material is stably melted, mix and cool to obtain the coating inner layer.

8. The method for preparing a cable for new energy vehicles according to claim 1, characterized in that: The step S3 comprises: S3.1, drying the thermoplastic resin matrix at a temperature of 80-100°C for 4-6 hours to reduce the moisture content to ≤0.05wt%; S3.2, adding the anti-UV additive, the wear-resistant enhancer and the diluent to the thermoplastic resin matrix in sequence, premixing for 20 to 30 minutes at a speed of 1000 to 1500 rpm using a high-speed stirrer to obtain a resin mixed solution with a viscosity of 500 to 1500 mPa·s; S3.3, heating the resin mixed solution at a constant temperature, equipping with a rotating fixture, fixing the inner core wrapped with the coated inner layer with the intermediate grid layer on the fixture and slowly immersing it in the resin mixed solution, wherein the constant temperature of the resin mixed solution is 60-80°C, the rotation angle of the rotating fixture is 45-90°, the immersion speed is 1-3 mm / s, and the immersion time is 5-10 min; S3.4, after the immersion is completed, the inner layer of the coating is slowly removed, and a low-speed rotating device is used to perform a solution shedding operation, so that the thickness of the resin solution on the surface of the inner layer of the coating is 0.2-2 mm, wherein the rotation speed of the low-speed rotating device is 30-50 rpm; S3.

5. Place the inner layer of the coating after peeling off in a vacuum chamber for degassing. After degassing, place it in a hot air circulation curing furnace for low-temperature circulation pre-curing. After cooling, obtain a cable for new energy vehicles, wherein the degassing time is 3 to 5 minutes, and the curing temperature includes a first stage of 180 to 200°C, a second stage of 200 to 220°C, and a third stage of 220 to 250°C. The curing time of the first stage is 20 to 25 minutes, and the curing time of the second stage and the third stage is 10 to 20 minutes.

9. A cable for new energy vehicles, characterized in that: The new energy vehicle cable is prepared by the preparation method of any one of claims 1 to 8, wherein the new energy vehicle cable comprises an internal conductor, a coating inner layer, an intermediate mesh layer and a protective outer layer which are sequentially stacked, wherein the internal conductor is used to realize signal or energy transmission, the coating inner layer is used to protect the internal conductor of the new energy vehicle cable, the intermediate mesh layer is used to improve the thermal conductivity, electrical conductivity and structural strengthening capabilities of the new energy vehicle cable, and the protective outer layer is used to improve the durability of the new energy vehicle cable to ensure the long-term use performance of the cable in a complex environment.

Citation Information

Patent Citations

  • Patterning on surface with high thermal conductivity materials

    CN101460678A

  • Low smoke zero halogen flame retardant material for high voltage cable jacket

    CN102952313A

  • Halogen-free flame-retardant coating composition for cable

    CN106397955A

  • Cable material and preparation method and application thereof

    CN108641267A

  • Damp-heat-resistant insulating material, preparation method thereof and environment-friendly electric wire

    CN119570148A